A Theory of Regret - Price, Brian (Duke University Press, 2017)
In A THEORY OF REGRET Brian Price takes up regret as a useful political emotion and, surprisingly, as a way to understand bureaucracy. Drawing on the work of Hannah Arendt, Aristotle, and Heidegger, as well as examples from film, Price presents a philosophical reflection on the transformative qualities of regret insofar as it provides opportunities to re-evaluate our commitments and to recognize that we are judging ourselves and others differently. According to Price, the impersonality and indifference of bureaucracy is often seen as a structure to forestall regret; however, interacting with bureaucrats can be a pathway for thinking about how to redress past wrongs.